Optimization of Composite Briquette Made From Sawdust/Rice Husk Using Starch and Clay Binder - Chukwuneke, Jeremiah; Umeji, Anthonyi; Obika, Echezona; Fakiyesi, Oladapo (International Journal of Integrated Engineering, 2021)
In this study, the physical properties and optimization of briquettes made from rice husk and sawdust were carried out. The bio-waste material of homogeneous particle sizes of 0.5mm and two binders of 90:10 percentage compositions which were sun-dried, prepared and compressed for the production of the briquettes. Energy valuation of the briquettes was carried out using a bomb Calorimeter. Response surface methodology was implored in the optimization of the energy values from rice husk/sawdust composite briquettes with clay and starch as binders, after which a composite briquette made from mahogany sawdust/rice husk was produced using the optimal condition values of 15% binder starch, 28% rice husk and 9Mpa compaction pressure. The results indicated that composite briquettes of mahogany sawdust and rice husk produced using starch gave the maximum energy value of 5.69kcal/g whereas those made with clay gave the least calorific value of 3.35kcal/g. This indicates that briquette from a composite of Mahogany sawdust/rice husk is, as a result, more appropriate for starting and retaining the fire for cooking and other domestic heating.